2009
DOI: 10.1016/j.ccr.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 Attenuates β-Catenin/T Cell Factors in Intestinal Tumorigenesis

Abstract: Due to a mistake made during manuscript preparation, the Supplemental Data for this article listed incorrect sequences for the primer sets for methylation-specific PCR (MSP). The correct sequences are given below. These corrections do not affect the findings or conclusions of the study.Primer sets used for detection of methylated DNA were 5 0 -ataaagagaaattaggcgc-3 0 and 5 0 -ataaccctcgaaaaacgcg-3 0 (M3), 5 0 -gatgttt gtttaggtcgtagcggtc-3 0 and 5 0 -ccaaactcgaaattcgccgta-3 0 (M2), and 5 0 -tgcgattggttgcgtttcgc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 0 publications
4
84
0
Order By: Relevance
“…Among these is RUNX3 that codes for runt-related transcription factor 3, which modulates both the transforming growth factor (TGF)-β [81] and the Wnt/β-catenin signaling pathways [82]. Runx3 –/– mice exhibit gastric epithelial proliferation due to decreased apoptosis and reduced sensitivity to the growth inhibitory cytokine, TGF-β.…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these is RUNX3 that codes for runt-related transcription factor 3, which modulates both the transforming growth factor (TGF)-β [81] and the Wnt/β-catenin signaling pathways [82]. Runx3 –/– mice exhibit gastric epithelial proliferation due to decreased apoptosis and reduced sensitivity to the growth inhibitory cytokine, TGF-β.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Thus, suppression of RUNX3 expression leads to aberrant signaling of both pathways, which are commonly dysregulated in colonic carcinogenesis. Loss of function of RUNX3 has significant and constitutive effects on the expression of its target genes, which may then contribute to CRC development [76, 82]. Decreased expression of RUNX3 mRNA due to epigenetic hypermethylation of the RUNX3 promoter occurs in a range of human CRC cell lines [84].…”
Section: Dna Methylationmentioning
confidence: 99%
“…The role of RUNX3 in melanoma progression is not known but may follow similar mechanistic pathways as found in other cancers. A recent study has found that RUNX3 forms a ternary complex with β-catenin/TCF4 and attenuates Wnt signaling (40), which is known to play an important role in melanoma progression (41). …”
Section: Discussionmentioning
confidence: 99%
“…( e ) RUNX3 expression is decreased within mouse gastric mucosa early after infection with H. pylori NCTC11637CagA-positive strain. Immunohistochemistry for RUNX3 was performed as previously described (Ito et al , 2008) on gastric mucosa harvested from INS-GAS mice infected with WT or cagA -deficient NCTC11637 H. pylori strains 48 h after inoculation. Representative staining of RUNX3 is shown for WT (left panel) or cagA -deficient mutant (right panel)-infected mice.…”
Section: Figuresmentioning
confidence: 99%